Do gymnasts experience symmetrical limb loading when performing foundation gymnastics skills? - Campbell, R. A.; Bradshaw, E. J.; Ball, N.; Hunter, A.; Spratford, W. (ISBS Proceedings Archive (Michigan), 2019)
.Uneven asymmetrical landings in artistic gymnastics is considered a risk factor for injury. The aim of this research was to investigate if gymnasts experience asymmetrical upper and lower limb loading when performing foundation gymnastics skills on floor. Sixteen competitive level gymnasts (male= 8, female= 8) performed seven different gymnastics skills while wearing four inertial measurement units located bilaterally on the distal forearm and tibias. Every gymnastics skill showed significant inter-limb asymmetry (range z= -5.8, -6.0, p